Relative stereochemical assignment of C-33 and C-35 in the antibiotic gladiolin. Issue 38 (20th September 2018) - Perry, Christopher; Sargeant, Jacob R.; Song, Lijiang; Challis, Gregory L.
Abstract: Gladiolin is a macrolide antibiotic isolated from Burkholderia gladioli BCC0238 with promising activity against Mycobacterium tuberculosis, including several multidrug resistant strains. The configuration of all but one of the stereogenic centers of gladiolin has previously been elucidated using a combination of NOESY NMR experiments and predictive sequence analysis of the polyketide synthase responsible for its assembly. However, it was not possible to assign the configuration of the C-35 methyl group using such methods. Here we report the synthesis of C-33/C-35- syn and C-33/C-35- anti mimics of the C-30 to C-38 fragment of gladiolin from ( R ) and ( S )-citronellol, respectively. Comparison of HSQC NMR data for the mimics and the natural product showed that the C-35 methyl is anti to the C-33 hydroxyl group, indicating that gladiolin has the 35 S configuration. Graphical abstract: Image 1